Implementation of Creative Dance Learning Techniques in Developing Students' Creativity in Extracurricular Activities at Madrasah Ibtidaiyah Darussalam Jelutung, Jambi City - Juwita Ulya Annisa; Saidah Ahmad; Jetra Viktoria (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the implementation of creative dance learning techniques in developing students' creativity in extracurricular activities at MI Darussalam Jelutung, Jambi City. Using a descriptive qualitative approach, data were collected through observations, interviews, and documentation involving instructors and fourth-grade students. The results indicate that the learning process is carried out through stages of demonstration, exploration, improvisation, and simple composition. These techniques are proven to increase self-confidence, courage in expression, and the students' ability to create imaginative movement variations. Despite obstacles such as limited ideas among some students, the implementation of these techniques effectively supports the development of creativity as a 21st-century competence at the elementary school level.